Racism, Eh?: A Critical Inter-Disciplinary Anthology of Race and Racism in Canada - Nelson, Charmaine; Nelson, Camille A. (Captus Press, 2004)
"Racism, Eh?" is the first publication that examines racism within the broad Canadian context. This anthology brings together some of the visionaries who are seeking to illuminate the topics of race and racism in Canada through the analysis of historical and contemporary issues, which address race and racism as both material and psychic phenomena. Fundamentally interdisciplinary in nature, this text will be an invaluable resource for undergraduate and graduate students, academics studying or practicing within the Humanities and the Social Sciences, and anyone seeking information on what has been a little explored and poorly understood Canadian issue."–Publisher's description. Contents: Part 1 Institutional Racism – 1 Penn and Teller Magic – 2 Lance Belanger's Tango Lessons – 3 The Black Occupational Structure in Late-Nineteenth-Century Ontario – Part 2 Crime and Justice – 4 Raising Raced and Erased Executions in African-Canadian Literature – 5 Examining Racism and Criminal Justice – 6 Criminological Research on "Race" in Canada – Part 3 First Nations – Of Land, Law and Power – 7 Across a Boundary of Lava – 8 Treaty Federalism – 9 Navigating Discrimination – Part 4 Race, Place and Nation – 10 Adrift in the Diaspora – 11 Racism Between Jews – 12 Local Colour – Part 5 Complexity of Intersectionallity and Performance of Racial Identity – 13 Speak White! – 14 Jack Canuck Meets John Chinaman – 15 Performing Desire – Part 6 Popular Culture – 16 Race In-Out of the Classroom – 17 Other Canadian Voices – 18 (Re)Visioning Histories – Part 7 Production and Representation – 19 Each Sentence Realized or Dreamed Jumps Like a Pulse with History and Takes a Side – 20 Articulating Spaces of Representation – 21 The "Hottentot Venus" in Canada – 22 Racial Recognition Underpinning Critical Art – Part 8 Multiculturalism – 23 But Where Are You REALLY From? – 24 Social Cohesion and the Limits of Multiculturalism in Canada – 25 Racialising Culture-Culturalising Race – 26 Re-articulating Multiculturalism.
Keywords: Racism – Canada